Synergistic Organoboron/Palladium Catalysis for Regioselective N-Allylation of 2-Pyridones, 4-Pyridones, and Related Ambident Heterocycles - Yatzoglou, Giorgos; Zambri, Matthew T.; Desai, Shrey P.; Taylor, Mark S. (Synlett, 2023)
The use of a boronic acid co-catalyst along with a palladium complex enables efficient dehydrative couplings of allylic alcohols and tautomerizable heterocycles. The protocol has been applied to achieve N-allylations of 2-pyridones, 4-pyridones, 4-pyrimidinones, and their benzofused derivatives.
Keywords: allylation; boronic acids; heterocycles; palladium; regioselectivity